2019
DOI: 10.3389/fcvm.2019.00032
|View full text |Cite
|
Sign up to set email alerts
|

Three in a Box: Understanding Cardiomyocyte, Fibroblast, and Innate Immune Cell Interactions to Orchestrate Cardiac Repair Processes

Abstract: Following an insult by both intrinsic and extrinsic pathways, complex cellular, and molecular interactions determine a successful recovery or inadequate repair of damaged tissue. The efficiency of this process is particularly important in the heart, an organ characterized by very limited regenerative and repair capacity in higher adult vertebrates. Cardiac insult is characteristically associated with fibrosis and heart failure, as a result of cardiomyocyte death, myocardial degeneration, and adverse remodeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 321 publications
(398 reference statements)
1
54
0
8
Order By: Relevance
“…Injury to the heart can result in the amplification of resident cardiac fibroblasts, the transformation of endothelial/epithelial cells to fibroblasts, and even the recruitment of hematopoietic cells to the site of injury and their transformation into cardiac fibroblasts and myofibroblasts [49]. This cascade of complex cellular and molecular interactions determines successful recovery or inadequate repair of the damaged tissue in the heart.…”
Section: Role Of Opn In Cardiac Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Injury to the heart can result in the amplification of resident cardiac fibroblasts, the transformation of endothelial/epithelial cells to fibroblasts, and even the recruitment of hematopoietic cells to the site of injury and their transformation into cardiac fibroblasts and myofibroblasts [49]. This cascade of complex cellular and molecular interactions determines successful recovery or inadequate repair of the damaged tissue in the heart.…”
Section: Role Of Opn In Cardiac Fibrosismentioning
confidence: 99%
“…These activated fibroblasts and myofibroblasts become the source of ECM proteins necessary for scar formation and healing of infarcted regions of the heart [6]. However, failure to terminate this wound-healing process results in persistent activation of fibroblasts and excessive cardiac remodeling associated with cardiomyocyte death, myocardial degeneration, impaired ventricular relaxation, and overall cardiac decompensation [8,10,15,49]. This cascade of events has been suggested to further increase the release of OPN from cardiomyocytes, thereby increasing OPN expression in infarct as well as non-infarct regions of the heart post-MI [56].…”
Section: Role Of Opn In Cardiac Fibrosismentioning
confidence: 99%
“…[ 168,169 ] An ambitious goal in modern cardiology is to develop a means of regenerating the injured myocardium following MI since the human myocardium has poor intrinsic regenerative capability. [ 167,169,170 ] Significantly, electro‐stimulation studies in the repair of percutaneous skin wounds has demonstrated that the polarization status of macrophage populations is amenable to electro‐stimulation and this stimulus also results in migration of macrophages into damaged tissue where they elicit a repair response. [ 151,160,162 ] Such electro‐stimulatory procedures may also be suitable for the regeneration of MI tissue and the recovery of heart function following heart attack.…”
Section: Electro‐stimulation and Tissue Repairmentioning
confidence: 99%
“…Although resident cardiac immune cells have been shown to contribute to inflammation and fibrosis, in general they are believed to have a minimally inflammatory role and promote angiogenesis [35]. Better understanding of the interactions between CMs, CFs and immune cells following acute injury is important to guide future research [36].…”
Section: Cardiac Fibroblasts and Resident Immune Cellsmentioning
confidence: 99%